KETERGANTUNGAN MASYARAKAT MISKIN DAN DILEMA KEBIJAKAN SOSIAL: STUDI PADA IMPLEMENTASI BANTUAN SOSIAL PROGRAM KELUARGA HARAPAN - Haliim, Wimmy; Hakim, Andy Ilman (Fakultas Politik Pemerintahan IPDN, 2024)
ABSTRACT The problem of poverty is often related to the bureaucracy's ability to accelerate the resolution and alleviation of poverty. One social policy that seeks to increase poor families' access to basic services and encourage improved quality of life is the Family Hope Program (PKH). The irony is that there are still many people who are trapped in the trap of poverty, and this gives rise to new problems in the implementation of PKH. Using qualitative research methods located in Malang Regency, this article attempts to identify problems in the implementation of social policies, as well as their impact on poor communities. The research results show several paradoxical impacts, such as the dependence of the poor on government assistance and leading to repeated cycles of poverty, as well as an increase in PKH recipients every year. The author's analysis explains that this is due to the deviant behavior of actors who take advantage of the weaknesses of the PKH implementation system to gain personal benefits outside the program vision. The actors' orientation leads to destructive behavior such as corruption by PKH facilitators and misuse of social assistance by Beneficiary Families (KPM). This phenomenon not only illustrates bureaucratic and social pathology but creates dependency and becomes an obstacle in the efforts of poor people to escape the trap of poverty. Keywords: Poverty, Pathology, Social Policy.